Consumer perception in four farmers’ markets, Costa Rica - Arboleda Julio, Esteban (2018)
This article is intended to describe the perspectives of consumers who attend the farmers’ market (FM) in Tibás, Santo Domingo, San Isidro and Barva in the province of Heredia, Costa Rica, based on surveys that were carried out in 2014 and 2015. The methodology was based on the dynamism and nature of the farmers’s market, allowing the qualitative and quantitative analysis of the variables that describes the consumer behavior. A general overview of the operation of FMs administered by Cantonal Agricultural Centers (CACs) was obtained, after which simple random sampling was used to select different FMs and consumers for further analysis. A statistical description of demographic and socioeconomic aspects of FM consumers is included in the analysis of the information obtained and in the synthesis of results. The study found that certain generalized problems are related to the lack of infrastructure, safety and food quality, among other issues. On the other hand, consumers say they buy legumes, greens and fruits as priority products. The FAs are rated by consumers as acceptable and the stands are rated as regular. Both the fairs and stands are in a vulnerable line of competitiveness suggesting to work in strategic areas aimed at strengthening the cultural and historical aspects preferred by consumers.